LANGUAGE ANXIETY IN ONLINE EDUCATION - Seidikenova, A.; Malshy, M.; Akkari, A. (Farabi Journal of Social Sciences, 2020)
Abstract: Anxiety on the lessons of a foreign language - is a notion that is studied from the 1980s, but little research was conducted on the topic Language Anxiety distance and online learning. In the literature review were considered the following issues: (a) What is language anxiety in the classroom of a foreign language? (b) What are the main results of studies of the level of anxiety in foreign language lessons? (c) The article discusses a test system for determining the level of linguistic anxiety in foreign language lessons, which was developed by Horwitz and Cope (1986). Language anxiety on the classes of foreign language may have negative impact on process of the second language acquisition. Current article refers to the problem of language anxiety in teaching foreign language at distance and possible solutions of decreasing language anxiety. Psychological aspect is a crucial part of educational process that leads to successful learning. Recommendations provided in the following article may help students to feel less isolated, less anxious and to establish contacts with their teacher and peers. The article concludes with suggestions for future research on online language anxiety. Key words: language anxiety, online learning, distance learning, language learning, online technologies, teaching methods, online pedagogy, methodology, teaching foreign languages, remote learning.